FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEBERHASILAN CARDIOPULMONARY RESUSCITATION (CPR) PADA PASIEN CARDIAC ARREST DI IGD RSUD PASAR MINGGU - Winda Narilia Esnawanti, (2023)
The incidence of cardiac arrest occurs a lot but few have examined the factors affecting it. This study aims to determine the factors affecting the success rate of (Cardiopulmonary Resuscitation) CPR patient in cardiac arrest in the emergency room Pasar Minggu Hospital. Crossectional research design with a retrospective approach. Samples were 123 patients who experienced cardiac arrest in the emergency room in the period 2020-2022, data collection using purposive sampling method. Data were taken from medical records using observation sheets. Of the 123 patients, 54 (43.9%) achieved ROSC and 69 (56.1%) did not achieve ROSC. The results of chi-square analysis and logistic regression showed that CPR duration and initial rhythm factors were associated with the success of ROSC (p value=0.000). The odds ratio showed that age, gender, comorbidities, time of occurrence and intubation measures were preventive factors for failure. In this study most patients experienced cardiac arrest at night where there were fewer officers than during the day. Initial rhythm PEA/asystole (non shockable) is caused by respiratory failure while delay in cardiac arrest detection can change the initial rhythm from VT/VF (shockable) to PEA/asystole (non shockable). Therefore, the researcher suggested adding officers to the night shift in the emergency room.